Efektivitas Media TV Edukatif Terhadap Partisipasi Siswa Dalam Pembelajaran Pendidikan Karakter - Bella, Regina Rita; Febriati, Farida; Irmayanti, Murlia; Wulandari, Sintia (LPPM UM Metro, 2026)
This research is focused on analyzing how effective Educational TV media is in enhancing student involvement in character education among fourth graders at SD Katolik Santo Yakobus. Design/methodology/approach: The study utilized a quantitative pre-experimental framework, specifically a one-group pretest-posttest model. The participants included 27 Grade 4 students from SD Katolik Santo Yakobus, chosen through total sampling. Data collection was carried out through systematic observation using a participation scale and a questionnaire that was validated by experts, along with Pearson product-moment correlation and Cronbach’s Alpha for checking reliability. The hypothesis was evaluated using the Wilcoxon Signed-Rank Test because of the non-normal distribution of data. Findings: The analysis revealed that the mean participation score rose significantly from 58. 74 (pretest) to 82. 59 (posttest), indicating an average increase of 23. 85 points. The Wilcoxon test resulted in Z = -4. 519 with an asymptotic significance (2-tailed) of 0. 000 (p < 0.05), showing a noteworthy increase in student involvement following the introduction of Educational TV media. The calculation of effect size with Cohen’s d yielded a figure of 1. 85, which is recognized as an extremely large effect. These results indicate that Educational TV media plays a crucial role in boosting student engagement in character education activities.